Pengaruh penerapan treasure map sebagai media pembelajaran matematika terhadap keaktifan siswa SD - Tri Wulandari; Zainnur Wijayanto (Universitas Sebelas Maret, 2025)
Mathematics at the elementary school level is often assumed to be a difficult and unvaried subject. The lack of interest and motivation of students in learning mathematics can have an impact on the low potential in the form of their learning activeness. This study has the main objective, namely to analyze the effect resulting from the application of Treasure Map learning media on the activeness of grade 6 students at SDN 3 Glodogan in the 2024/2025 academic year specifically in mathematics subjects. The method used in this research is pre experimental design through one group pretest-posttest design with quantitative data processed through the SPSS application. Data collection that researchers do with observation, questionnaires, and written tests. The results of the research conducted are the use of Treasure Map learning media in math fraction material has a positive and significant effect on the learning activeness of each student. The effect caused is able to influence the increase in learning activeness effectively and efficiently according to the ability of each student.